First results from in situ transmission electron microscopy studies of all-solid-state fluoride ion batteries - Anji Munnangi (Journal of Power Sources, 2020)
A focused ion beam (FIB) system is used to fabricate a micron-sized all-solid-state fluoride ion cell from a bulk battery for in situ transmission electron microscopy (TEM) testing. The bulk battery is based on a La0·9Ba0·1F2.9 solid-state electrolyte with a nanocomposite of Cu/C as a cathode and a nanocomposite of MgF2, Mg, La0·9Ba0·1F2.9 and C as an anode. The evolution of the morphology, structure, and composition of the electrodes and their interfaces with the electrolyte is characterized using in-situ TEM during electrochemical cycling. The high-resolution transmission electron microscopy (HRTEM) and scanning transmission electron microscopy-energy dispersive X-ray (STEM-EDX) analysis of the cathode-electrolyte interface reveal the expected formation of CuF2 phase during charging. During cycling, grain growth of Cu in the cathode ingredients and Cu diffusion from the cathode into the electrolyte are observed in addition to void formation.